PENERAPAN METODE PENGAJARAN AUDIOVISUAL PADA PEMBELAJARAN TEKS MELALUI MODEL PjBL DI SEKOLAH - Rizqien, Nadhifatur; Mujianto, Gigit (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research aims to determine the steps in implementing audiovisual methods with a project-based learning model at school. This study uses a qualitative method. The data source in this research is a secondary data source, which comes from a video of teaching practice from a teacher who is taking a professional course or PPG. The results of this research found two forms of speech related to the presentation of learning media, two utterances explaining the project carried out by the teacher, and two utterances related to teacher development and direction. And the results found that there are six stages of implementing the project-based learning (PjBL) learning model in learning. The first stage is determining the basic question or project. The second stage is project design planning. The third stage is preparing the project schedule. Fourth stage Completion of the project with monitoring. Fifth stage Testing project results. And the sixth stage is Evaluation. Learning using the PjBL model provides benefits for students to think critically, creatively, and provides challenges to students so that they gain satisfaction by discovering new knowledge for themselves.